Forty years of dynamics: Population trends and habitat changes of the Black-necked Crane (Grus nigricollis) in China - Aiping Jiang; Tiantian Jin; Di Zhang; Qianwen Li; Boran Zhu; Qidong Peng; Junqiang Lin (Global Ecology and Conservation, 2025)
Over 95 % of Black-necked Cranes (Grus nigricollis) are found on the Qinghai-Tibet Plateau and the Yunnan-Guizhou Plateau. Due to effective conservation efforts, the population of the Black-necked Crane has experienced significant growth. However, a comprehensive review of their breeding and wintering habitats remains lacking, and the relationship between population dynamics and habitat changes is not yet fully understood. This study, therefore, analyzes population trends and habitat alterations across 13 key nature reserves in China. It explores the underlying factors contributing to the species' remarkable population recovery, summarizes current conservation strategies, identifies major threats, and provides recommendations for future conservation efforts. The results revealed the following: (1) The population of Black-necked Cranes increased from approximately 5600–6000 individuals in the early 1990s to 17,389–17,610 individuals in 2022, with 92 % of the reserves exhibiting positive population growth. (2) Breeding habitats were primarily composed of grasslands, wetlands, and water bodies, with a notable shift from wetland degradation to recovery. The combination of habitat type and habitat change significantly affected the population in breeding areas, with grasslands being the most significant habitat type influencing population changes (p = 0.03). Wintering habitats were mainly croplands, grasslands, and water bodies, with a significant decline in cropland availability. While habitat type and habitat change did not significantly affect population changes in wintering areas (p = 0.70), the increase in population is largely attributed to effective human conservation measures. (3) Despite conservation successes, the Black-necked Crane remains threatened by climate change and human activities. Economic development and reserve management must fully consider these impacts to ensure the species' long-term survival. This study provides a scientific basis for the conservation of Black-necked Cranes and recommends the establishment of a coordinated protection mechanism to address future challenges.